THE ROLE OF HEALTH EDUCATION PROGRAM HEALTH PROGRAM TOWARD KNOWLEDGE OF DHF IN KEDURAHAN SANANWETAN BLITAR CITY - Purwatiningsih, Rini; Ratna Wardani; Intan Fazrin (Universitas STRADA Indonesia, 2018)
Dengue hemorrhagic fever (DHF) is an infectious disease by dengue virus that is transmitted through the bite of the Aedes Aegypti mosquito, characterized by sudden high fever accompanied by manifestations of bleeding and tends to cause shock and death. The design of this research is quantitative pre-post experimental research with one group pre-test and post-test design. The focus of the research is to analyze health education on the role of health education program at the health center on the knowledge of DHF in Gedog District Sananwetan District, Blitar City before and after the intervention. Total population of 50 respondents with Simple Random Sampling technique and obtained a sample of 44 respondents. The results showed that the majority of respondents had less knowledge in the health category before being given the health education program at the puskesmas program with 24 respondents (54.5%). While the majority of respondents had sufficient knowledge in the category after being given the health education program at the puskesmas program by 21 respondents (47.7%). The Wilcoxon analysis results show that the p-value of 0,000 <0.05 then H0 is rejected so it is concluded that there is an influence of health education in the health center program on DHF knowledge in Gedog Village, Sananwetan Sub-District, Blitar City. With these results it is expected that respondents will conduct monitoring in places that would be mosquito habitat, after that bury items that can become puddles, then drain the tub and close the water reservoirs. Besides that, don't forget to sprinkle the abate on the well. Respondents can also prevent 4M Plus so that mosquitoes cannot breed around our homes.